(untitled) (Derna Academy Journal for Applied Sciences, 2026)
The development of digital literacy in children is strongly influenced by the design of web search interfaces. Most mainstream search engines focus on adult users and do not align with children’s cognitive, linguistic, and social abilities. This systematic review examines how current web search interfaces support children’s information-seeking behaviors. It also identifies gaps between design intentions and the needs of young users. A comprehensive search was conducted across major databases, including Semantic Scholar, Scopus, Springer, ACM, and PubMed. After screening and deduplication, 27 high-quality studies were included. These studies cover empirical research, interface design, digital literacy, and child-friendly search tools. Findings show that children struggle to formulate effective queries, interpret results, and evaluate credibility. Misunderstandings of how search engines work contribute to these difficulties. Adaptations such as voice-based interfaces, gamification, and visual aids can improve engagement and performance. However, real-world use is still dominated by Google and Bing. Emerging technologies like conversational agents, AI-powered chatbots, and collaborative search models offer potential to reduce cognitive load and provide better support. These tools also introduce challenges related to transparency, trust, and educational alignment. Overall, current web search interfaces do not fully meet children’s needs. The review provides insights for researchers and designers. It highlights the importance of developing search systems that are literacy-aware, developmentally appropriate, and equitable for young users.